Using Cooperative Learning In Teaching Critical Thinking In Reading - Anit Pranita Devi; Bachrudin Musthafa; Gin Gin Gustine Gustine (University of Kuningan, 2015)
This study investigates how cooperative learning facilitates students in learning critical thinking in reading and to find out the benefits and challenges during the implementation of cooperative learning in one vocational school in Cimahi. A case study is utilized by using instruments of classroom observations, questionnaires, semi structured interview and students’ written tests. The findings show that the implementation of cooperative learning facilitates students develop their critical thinking and enhance critical thinking dispositions in reading. Three features which contribute to the development of students’ critical thinking in reading are: the encouragement of student-student interaction; the provision of group purposes; and the provision of stimulus to the students’ development of thought and ideas. The aforementioned features promote benefits which involved higher motivation and involvement, increased opportunity for language use, and developed interpersonal relationship. Nevertheless, these benefits are constrained by the availability of time, students’ English proficiency, and students’ contribution to the groupwork. It is recommended that further researchers conduct the similar study in a longer period to make sure that the key elements of cooperative learning are well-structured.Keywords: cooperative learning, critical thinking